Greenhouse gas emissions of 100% bio-derived polyethylene terephthalate on its life cycle compared with petroleum-derived polyethylene terephthalate. (10th September 2018) - Semba, Toshiro; Sakai, Yuji; Sakanishi, Tatsuya; Inaba, Atsushi
Abstract: Polyethylene terephthalate widely used as fibre materials and container packaging materials is produced by the condensation polymerisation of monoethylene glycol and terephthalic acid. Monoethylene glycol and terephthalic acid have been conventionally manufactured using petroleum as the raw material, however monoethylene glycol has recently been manufactured from biomass as the raw material from the viewpoint of reducing carbon dioxide emissions. Recently, a process for manufacturing para-xylene from ethanol was developed, and 100% bio-derived polyethylene terephthalate using terephthalic acid produced by para-xylene obtained from bio-based ethanol and bio-based monoethylene glycol is currently under development. However, a study of calculating greenhouse gas emissions from 100% bio-derived polyethylene terephthalate has not been reported. In this study, greenhouse gas emissions of 100% bio-derived polyethylene terephthalate were calculated using material balance data from the production process of para-xylene from ethanol under development. This methodology complied with the life cycle inventory study of ISO 14040 (2006) and 14044 (2006). As the result, greenhouse gas emissions of 100% bio-derived polyethylene terephthalate, assuming that bio-para-xylene is produced by 20% of sugarcane and 80% of corn, decreased by 24.0% compared with those of petroleum-derived polyethylene terephthalate. In addition, the greenhouse gas emissions of 100% bio-derived polyethylene terephthalate using bio-based ethanol obtained only from sugarcane as the raw material of bio-based para-xylene were 1.88 kg-CO2e /kg-polyethylene terephthalate, which demonstrates the potential to decrease greenhouse gas emissions from petroleum-derived polyethylene terephthalate by about 58%.